2017
DOI: 10.1017/s0022109016000788
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamics of Performance Volatility and Firm Valuation

Abstract: We construct a model to illustrate the dynamics of cash-flow volatility (CFV) and firm valuation. As a firm progressively invests in its growth opportunities, its book value increases and catches up with its market value, reducing the valuation multiple (Q). CFV decreases because of the diversification effect of investing in more market segments. We document a positive CFV-Q association, which varies with firm size, investment opportunities, and the correlation across market segments. Empirical findings strong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
16
1
Order By: Relevance
“…Information about the company's cash availability is a positive signal that can make investors react positively because of the guaranteed financial stability of the company. The results of this study are in line and consistent with research conducted by Chi & Su (2017), who found that high cash flow volatility will improve investors' valuation of the company. But the results of this study are not in line and are not consistent with research conducted by Iyer & Harper (2017) and Altuntas, Liebenberg, Watson, & Yildiz (2017).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Information about the company's cash availability is a positive signal that can make investors react positively because of the guaranteed financial stability of the company. The results of this study are in line and consistent with research conducted by Chi & Su (2017), who found that high cash flow volatility will improve investors' valuation of the company. But the results of this study are not in line and are not consistent with research conducted by Iyer & Harper (2017) and Altuntas, Liebenberg, Watson, & Yildiz (2017).…”
Section: Resultssupporting
confidence: 91%
“…Research conducted related to cash flow volatility and investor reaction was conducted by Iyer and Harper (2017), who found that high cash flow volatility was more likely to be surprising which resulted in investors acting negatively, this is in line with Altuntas et al (2017), who found that cash flow volatility had a negative effect on firm value. However, this research contradicts Chi & Su (2017), who found that cash flow volatility has a positive relationship with firm value, especially in large, longstanding companies.…”
Section: Introductioncontrasting
confidence: 90%
“…If we segment company age within categories, as in Table 6, we observe that from 10 to 20 years of company age the perpetuity 2 coefficient (number of compound years of company existence needed to produce FCF, net profit, or dividend) decreases, indicating that in the early years, companies expect to exist for longer than 20 years (coefficient lower than the ones for 10 year, for all drivers). This is clear evidence of the high expectations of value associated with a young company, along the lines of Chi et al (2017). Although liabilities of age can occur for young firms, greater growth expectations lead company values to approach almost full perpetuity in case of dividends, a square root in the case of FCF, and near this value for net income.…”
Section: ( 1 9 )mentioning
confidence: 90%
“…The independent variable, firm age, is measured as the number of years since a firm's listing, which is a proxy for its lifecycle (Fama and French, ; Chi and Su, ). The dynamics of growth options include two variables: the intensity of capital expenditure (Purnanandam and Rajan, ) and the intensity of R&D investment (Kumar and Li, ), which are used as proxies for the exercising and the creating of growth options, respectively.…”
Section: Data and Variablesmentioning
confidence: 99%
“…Second, this paper is of relevance to the literature focusing on the roles of investment opportunities or growth options on firm valuation (Kogan and Papanikolaou, ; Kraft et al ., ). A number of papers about corporate lifecycle argue that the decline of firm valuation is caused by the decrease of investment opportunities, but there is still considerable but inconsistent evidence that capital expenditure has a positive effect on firm valuation (McConnell and Muscarella, ; Trueman, ; Rountree et al ., ; Chi and Su, ). Our paper finds that, for firms with a downward trend of firm valuation over time, capital expenditures in lagged years have a negative effect on firm valuation.…”
Section: Introductionmentioning
confidence: 97%